TRANSFORMING CUSTOMER EXPERIENCE: THE ROLE OF AI IN CCaaS - Vipin Kalra (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
The evolution of Contact Center as a Service (CCaaS) represents a transformative shift in customer service operations driven by artificial intelligence and cloud technologies. This comprehensive article explores how CCaaS solutions revolutionize traditional contact center models through advanced technologies, including natural language processing, machine learning algorithms, and real-time analytics. The article examines the implementation challenges, best practices, and emerging trends in CCaaS adoption, highlighting the critical role of strategic planning, technology selection, and change management in successful deployments. Through a detailed examination of market research and industry implementations, the analysis demonstrates how CCaaS solutions enhance customer experience, improve operational efficiency, and deliver substantial business intelligence benefits while addressing key technical integration, data security, and organizational adaptation concerns.